Capacity building within urban climate resilience in the Global South – a literature review - Wieszczeczynska, Katarzyna Alicja; Tollin, Nicola; Spaliviero, Mathias (Frontiers in Sustainable Cities, 2024)
Capacity building for urban climate resilience is essential for strengthening both cities’ own capacities and multilevel governance, which are instrumental for the successful operationalisation of the Paris Agreement. Strengthening the capacities for planning, managing, and developing cities is required to support an urban resilient transition in a context of high complexity and uncertainty, especially in the Global South. The main objective for this article is to investigate the differences in understanding of capacity building in urban climate resilience in the Global South through literature review. Specifically, this paper investigates the main approaches, aspects, components, and end users for capacity building in the frame of urban climate resilience. The article identifies a set of Capacity Building Parameters and Enabling Factors which are Purpose, Transformative Capacity, Multi-actor, Participation, Knowledge and Learning, Transdiciplinarity as well as Data and Finance. The Capacity Building Parameters and Enabling Factors can serve as a basis to develop an analytical framework to assess existing capacity building initiatives and to support the development of new capacities for planning, management and developing cities for an urban resilient transition.